2013
DOI: 10.1161/hypertensionaha.113.01513
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy and Cardiometabolic Health in Adolescent Offspring

Abstract: An accumulating body of evidence suggests that offspring of mothers with preeclampsia have higher blood pressure during childhood and young adulthood compared to women without preeclampsia. However, the evidence with regard to offspring glucose metabolism and lipids is more scant. We examined whether maternal hypertensive disorders of pregnancy (preeclampsia and gestational hypertension) are associated with a range of cardiometabolic health measures in adolescent offspring. We included data for mother-offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 23 publications
11
120
0
2
Order By: Relevance
“…[9][10][11] Several studies have shown an association between maternal preeclampsia and elevated blood pressure (BP) in the offspring during childhood and adolescence. [12][13][14][15][16][17][18][19] Other studies have reported on glucose metabolism in the offspring of mothers with preeclampsia. [20][21][22] The aim of the present study was to determine, using the Quantitative Insulin Sensitivity Check Index (QUICKI), whether preeclampsia influences insulin sensitivity (IS) in the offspring of affected mothers.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Several studies have shown an association between maternal preeclampsia and elevated blood pressure (BP) in the offspring during childhood and adolescence. [12][13][14][15][16][17][18][19] Other studies have reported on glucose metabolism in the offspring of mothers with preeclampsia. [20][21][22] The aim of the present study was to determine, using the Quantitative Insulin Sensitivity Check Index (QUICKI), whether preeclampsia influences insulin sensitivity (IS) in the offspring of affected mothers.…”
Section: Resultsmentioning
confidence: 99%
“…The results of 2 studies suggest that maternal preeclampsia and gestational hypertension may both be associated with higher blood pressure in adolescence, but their findings suggested no association with fasting insulin, glucose, lipid levels, apolipoproteins, or inflammatory markers. 28,29 An intriguing question is whether the adverse cardiovascular risk profile can be attributed to genetic or behavioral risk factors common to mothers and their offspring or to intrauterine vascular damage or altered metabolism caused by fetal exposure to hypertension or preeclampsia. [30][31][32] There is evidence that preeclampsia and CVD share similar risk factors 33 and that cardiovascular risk factors before pregnancy seem to be positively associated with preeclampsia risk.…”
Section: Discussionmentioning
confidence: 99%
“…Children born to PE mothers are at higher risk of developing proteinuria, hypertension, CKD, metabolic syndrome and cardiovascular diseases [105][106][107][108][109]. Interestingly, these are the same diseases that are reported in the mothers, and the study group holds that not only the mothers but also the children should be followed in the long term, with modalities still to be clarified, also on the account of the organization of the health care system, and on the availability of general care or specialist care.…”
Section: Pe Occurring In Patients Without Any Previous or Present Sigmentioning
confidence: 99%